Strategies of the Baduy Community in Navigating Economic Fluctuations During the COVID-19 Pandemic - Yakin, Ikin Ainul; Ardiyansyah, Muhammad Ridho (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2023)
The COVID-19 pandemic has significantly impacted the global economy, and Indonesia is no exception. The economic decline in Indonesia has affected the entire nation, including the province of Banten. Amid this crisis, researchers have shown interest in studying the Baduy community's response to the pandemic. This research aims to determine if the Baduy community has been affected by the economic impacts of COVID-19, to explore the strategies they employ to mitigate these impacts, and to identify the values within Baduy society that help them navigate economic challenges. The research seeks to answer several key questions: Has the Baduy community been directly affected by the economic impact of COVID-19? What strategies does the Baduy community use to cope with these economic challenges? What values inherent in Baduy society help them avoid the adverse economic effects of the pandemic? To achieve these objectives, the research employs an ethnographic method well-suited for social science research. Ethnography emphasizes immersion, personal experience, and active participation, rather than mere observation, by researchers trained in this qualitative research approach. The findings reveal that the Baduy people perceive COVID-19 and its consequences as natural events willed by God. This perspective, combined with their simple lifestyle and values of gratitude, modesty, and contentment, helps the Baduy community remain calm and resilient in facing life's challenges. Their approach to living—avoiding luxury and accepting life as it comes—contributes to their ability to weather economic fluctuations during the pandemic